Design of a compact hexagonal structured dual band MIMO antenna using orthogonal polarization for WLAN and satellite applications - Aziz Dkiouak; Mohssine El Ouahabi; Alia Zakriti; Mohsine Khalladi; Aicha Mchbal (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In this paper, a compact dual band multiple-input multiple-output (MIMO) antenna system for WLAN and X-band satellite applications (2.4/9.8 GHz respectively) is proposed. On the top face of the substrate, two antenna elements with a size of 20 × 24 mm2 are placed side by side and fed with matched orthogonal micro-strip lines. The two antenna elements have orthogonal polarization which can reduce the mutual coupling between its ports. The designed antenna system is fabricated and measured to validate the simulation results. The impedance bandwidths are about 370 MHz (2.19 to 2.56 GHz) and 630 MHz (9.44 to 10.07 GHz), while the obtained isolation is greater than 14 dB at the operating bands. Furthermore, the envelope correlation is less than 0.052 and 0.008 at 2.4 and 9.8 GHz, respectively. Hence the diversity gain is higher than 9.98 in the frequency bands of interest.